Predictive Nephrotoxicity Profiling of a Novel Antifungal Small Molecule in Comparison to Amphotericin B and Voriconazole - Udawatte, Nadeeka S.; Kang, Sung Wook; Wang, Yue; Arumugam, Thiruma V.; Seneviratne, Chaminda J. (Frontiers in Pharmacology, 2020)
Background and Purpose Candida albicans is the major fungal species associated with superficial mucosal infections such as oral candidiasis as well as systemic mycoses with high morbidity and mortality. On top of the rising drug resistance, currently available antifungal agents have significant adverse effects. Nephrotoxicity is the major treatment complication associated with antifungal agents. Recently, we discovered a novel antifungal small molecule SM21 with promising antifungal activity. The present study aimed to comparatively evaluate the in vivo and in vitro nephrotoxicity of SM21 comparing with amphotericin B and voriconazole. Experimental Approach Nephrotoxicity of SM21 and its analogue were comparatively evaluated with Amphotericin B- AmB and voriconazole . Immortalized human kidney proximal tubule epithelial cells (HK-2) were used for in vitro analysis of nephrotoxicity using cytotoxicity assays and qPCR gene expression analysis (Kim-1/ HAVcr-1, CASP3). Sprague Dawley rat model was used to evaluate the nephrotoxicity in vivo using classical (SCr and BUN) and next-generation kidney injury urinary biomarkers (Kim-1, CLU, ALB, NGAL, β2M, and Cys C) alongside histopathological and immunohistochemical standards. Key Results AmB treatment showed a stronger cytotoxic impact on HK-2 viability and gene expression of cell death markers (Kim-1/ HAVcr-1, CASP3) compared with SM21 and SM21 analogue in vitro (P < 0.01). In vivo data further demonstrated that SM21 did not significantly increase classical as well as novel nephrotoxic biomarkers, and minimal renal tubular necrosis and abnormalities were observed (15 mg kg−1 BW/day). Conclusions and Implications SM21 had a significantly better safety profile in terms of nephrotoxicity with no major tubular epithelial abnormalities observed in kidney cells and no augmentation of kidney injury biomarkers compared to AmB. Kim-1 and CLU were the most sensitive biomarkers for detection of AmB-induced kidney damage. Future clinical trials should consider inclusion of these novel biomarkers as early indicators of acute kidney injury in antifungal-induced nephrotoxicity.